2008
DOI: 10.1007/s00723-008-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

High-Field Dynamic Nuclear Polarization for Solid and Solution Biological NMR

Abstract: Dynamic nuclear polarization (DNP) results in a substantial nuclear polarization enhancement through a transfer of the magnetization from electrons to nuclei. Recent years have seen considerable progress in the development of DNP experiments directed towards enhancing sensitivity in biological nuclear magnetic resonance (NMR). This review covers the applications, hardware, polarizing agents, and theoretical descriptions that were developed at the Francis Bitter Magnet Laboratory at Massachusetts Institute of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
242
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 323 publications
(256 citation statements)
references
References 58 publications
0
242
0
3
Order By: Relevance
“…These approaches have resulted in large signal enhancements and have enabled many experiments that would otherwise be impossible. [19][20][21][22][23] by Overhauser 25 and confirmed by Carver and Slichter, 26 has not been identified or utilized during the course of this renaissance. Although the possibility of an OE in insulator was discussed by Abragam, 27 the conventional wisdom is that Overhauser DNP is important only in systems with mobile electrons such as conductors (metals and low dimensional conductors) or in liquid solution.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…These approaches have resulted in large signal enhancements and have enabled many experiments that would otherwise be impossible. [19][20][21][22][23] by Overhauser 25 and confirmed by Carver and Slichter, 26 has not been identified or utilized during the course of this renaissance. Although the possibility of an OE in insulator was discussed by Abragam, 27 the conventional wisdom is that Overhauser DNP is important only in systems with mobile electrons such as conductors (metals and low dimensional conductors) or in liquid solution.…”
mentioning
confidence: 95%
“…These approaches have resulted in large signal enhancements and have enabled many experiments that would otherwise be impossible. [19][20][21][22][23] Nevertheless, with the exception of an early example on a 1D conductor, 24 the Overhauser effect (OE), which was the initial DNP mechanism proposed a) Current address: Institute for Physical and Theoretical Chemistry, Institute for Biophysical Chemistry and Center for Biomolecular Magnetic Resonance, Goethe University Frankfurt, 60438 Frankfurt am Main, Germany.…”
Section: Introductionmentioning
confidence: 99%
“…14,[17][18][19] Single crystals were harvested and polished to fit into a quartz capillary of 0.4 mm inner diameter for experiments at 5 T. For experiments at 0.35 T, a larger sample that fit into a 4 mm EPR sample tube was used. In order to suppress the 1 H NMR signal from trapped solvent, we used perdeuterated ethanol (Cambridge Isotope).…”
Section: Experimental Samplesmentioning
confidence: 99%
“…12 Initially, the primary application of DNP was preparation of polarized targets for neutron scattering experiments; 13 however, over the past decade, DNP has been used extensively to enhance the inherently low sensitivity of nuclear magnetic resonance (NMR) signals. [14][15][16][17][18][19] Enhancements on the order of 10 2 − 10 3 were made possible via the solid effect using narrow-line radicals 20-23 and cross effect using biradicals 24-27 as polarizing agents and high frequency gyrotrons as microwave sources. [28][29][30] The latter operate in the 140-560 GHz regime and enable DNP to be performed at magnet field strengths used in contemporary NMR experiments (5-20 T).…”
mentioning
confidence: 99%
“…For example, the presence of the optical excitation in this class of system may facilitate dynamic nuclear polarization [20,21]. Further, recent experiments have shown that the principal decoherence mechanism for nuclear spins that are controlled through their interaction with electron spins is caused by that very same interaction [22].…”
Section: Introductionmentioning
confidence: 99%